Evaluation of diatomaceous earth on production, anatomical traits and quality of eggs in Japanese quail - Gilani, Ali; Hajati, H.; Seifi, S.; Sayrafi, R. (The Iraqi Journal of Veterinary Medicine, 2019)
An experiment has been carried out to evaluate a diatomaceous earth on performance and egg traits of Japanese quail. The diatomaceous earth used in the current trial was food grade which produced in Germany and is listed Generally Regarded As Safe. Eighty layer Japanese quail were randomly divided into 2 treatments from 16-20 weeks of age. Each treatment consisted 4 replicates (pens) of 10 birds each. The first treatment (control) contained a standard recommended diet with no added diatomaceous earth. The second treatment was the basal diet of the first treatment plus 1.5% diatomaceous earth in the feed. Feed and water were offered ad libitum from days 1 to 140. Egg production per pen was recorded daily. Egg traits were measured at the end of each week during experimental period. Utilization of diatomaceous earth did not have a pronounced effect on the production parameters and weight of egg, albumen, and shell, but significantly improved yolk size